Al-Qur'an, Orientalisme dan Luxenberg - Arif, Syamsuddin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2005)
The article focuses on issues related to the Qur'an, Orientalism and the controversial writer Christoph Luxenberg. A brief survey on studies by the Orientalist on the Qur'an is presented. It explains some critical confusions and misunderstandings by the Orientalist concerning the Qur'an especially that related to the authenticity of the Qur'an, as well as its writing and recitation tradition. The application of the philological methods used in the Biblical studies on the Qur'an is discussed. The article ends with a critical analysis on Luxenberg Die syro-aramaische Lesart des Koran: Ein Beitrag zur Entschliisselung der Koransprache.